Drivers and barriers to e-government adoption in Indian cities - Mercy Samuel; Gayatri Doctor; Perez Christian; Manvita Baradi (Journal of Urban Management, 2020)
This paper aims to understand the awareness and adoption levels of e-government services and identify the drivers and barriers to adoption of e-government services in a developing country. A technology adoption model is synthesized based on study of existent literature, and further empirically tested using field data from primary surveys in four Indian cities using suitable sampling strategy. In fulfilling the objectives, the approach also included capturing citizens' responses on awareness about online services, usage and satisfaction with select services for different modes, and perception of the e-government services to understand citizens' perspectives on e-government adoption. The primary finding of the study identifies drivers and barriers for adoption in a context of developing country. The study is limited to four cities in India. Technology adoption models require separate testing in different cultural contexts. The study findings have immense relevance for policy makers and implementers to strategize mechanisms of increasing the usage of e governance thereby making urban governance efficient and transparent. The research has its conceptual base in the theory of planned behavior and technology adoption model to derive a theoretical framework for e government adoption. The proposed technology adoption model introduces preference as a critical factor influencing e-government adoption in contrast to other previously known models.
Keywords: 710; Barriers; Drivers; e-Government; e-services; Indian cities; Municipal websites; E-Government; Innovationsakzeptanz; Kommunalverwaltung; Indien